Desktop apps with JavaScript (O'Reilly Media, 2019)
"Chances are high that you're already using desktop software built with JavaScript, apps like Slack, Visual Studio Code, or WhatsApp use the framework Electron to combine native code with the conveniences of Node.js and web technologies. Felix Rieseberg walks you through Electron, explaining both the up- and downsides of building apps with JavaScript. He covers the basics while building a small code editor live and examines how Microsoft, GitHub, Slack, and other companies collaborate to maintain Electron."--Resource description page